Targeted Metabolomics of the Phenylpropanoid Pathway in Arabidopsis thaliana using Reversed Phase Liquid Chromatography Coupled with Tandem Mass Spectrometry. Issue 4 (1st February 2017) - Jaini, Rohit; Wang, Peng; Dudareva, Natalia; Chapple, Clint; Morgan, John A.
Abstract: Introduction: The phenylpropanoid pathway is a source of a diverse group of compounds derived from phenylalanine, many of which are involved in lignin biosynthesis and serve as precursors for the production of valuable compounds, such as coumarins, flavonoids, and lignans. Consequently, recent efforts have been invested in mechanistically understanding monolignol biosynthesis, making the quantification of these metabolites vital. Objective: To develop an improved and comprehensive analytical method for (i) extensively profiling, and (ii) accurately quantifiying intermediates of the monolignol biosynthetic network, using Arabidopsis thaliana as a model system. Method: A liquid chromatography‐tandem mass spectrometry with electrospray ionization was developed to quantify phenylpropanoid metabolites in Arabidopsis wildtype and cinnamoyl CoA reductase1 (CCR1) deficient lines ( ccr1 ). Results: Vortexing at high temperatures (65°C) enhanced release of phenylpropanoids, specifically the more hydrophobic compounds. A pH of 5.3 and ammonium acetate buffer concentration of 2.5 mM resulted in an optimal analyte response across standards. Ion suppression was estimated using standard spike recovery studies for accurate quantitation. The optimized method was used to profile Arabidopsis wildtype and ccr1 stems. An increase in hydroxycinnamic acid derivatives and a decrease in the hydroxycinnamyl aldehydes and alcohols in ccr1 lines, supports a shift of flux from lignin synthesis to other secondary metabolites and phenylpropanoid derivatives. Conclusions: Compared to existing targeted profiling techniques, our method is capable of quantifying a wider range of intermediates (15 out of 22 in WT Arabidopsis stems) at low in vivo concentrations ( 50 pmol/g‐FW for certain compounds), while requiring minimal sample preparation. Copyright © 2017 John Wiley & Sons, Ltd. Abstract : The phenylpropanoid pathway is a source of a diverse group of compounds many of which are involved in lignin biosynthesis and serve as precursors to valuable compounds like coumarins, flavonoids, and lignans. Quantifying intermediates of the core monolignol biosynthetic network aids in the mechanistic understanding of lignin synthesis. To this end, we present an improved analytical method – based on liquid chromatography‐tandem mass spectrometry – for extensively profiling and accurately quantifying intermediates of the monolignol biosynthetic network in Arabidopsis.